Extending Single Threaded Compression To Multi-Threaded Compression - Tong , Sing Teik (2012)
This study describes about a parallel implementation of the deflate loss less compression program is described. The performance of the parallel implementation is compared to the sequential deflate program running on Intel Quad Core processor. The parallel deflate algorithm works by taking the input data and running them through the ZIV-Lempel algorithm simultaneously on multiple cores using threads. The results show that a speedup is achieved by using the parallel deflate program on systems with multiple cores. This will greatly reduce the time taken to compress large amounts of data.